Assessment of Anti Müllerian Hormone among Women with Polycystic Ovarian Syndrome in Khartoum State - Ali, Abdallah Eltoum; Bashir, Rowida M.Ibrahim; Hamza, Alneil M. (Jour Med Resh and Health Sci, 2024)
Polycystic ovary syndrome (PCOS) is the most common cause of chronic anovulation and hyperandrogenism in young women .POCS is a common endocrinopathy that accompanied with long term complications. The early diagnosis of this syndrome can prevent it. The study aim to assess serum levels of Anti Müllerian hormone among female with polycystic ovarian syndrome (PCOS). Sixty clinically diagnosed polycystic ovarian syndrome (PCOS), were chosen randomly from Reproductive Health Care Centre in Khartoum State as case group and thirty apparently healthy individuals as control group. Serum AMH and fertility hormones were measured by using ELISA technique. Results were analyzed using Statistical Package for Social Science (SPSS), computer programmed version 20. The mean serum levels of AMH was significantly increased in PCOS female patients when compare with control, (Mean± SD: 7.6±2.3 ng/ml versus 4.6±0.7 ng/ml), respectively with (P=< 0.001). There was a significant week positive correlation between Anti-Müllerian hormone levels and Luteinizing hormone levels (r=0.239; P= 0.023), and there was negative correlation between Anti -Müllerian hormone levels and Body Mass Index (r= -0.267; P= 0.039). The serum Anti Müllerian Hormone (AMH) measurement was significantly higher in PCOS patients, which could use for early marker diagnosis of PCOS patients.